Student’s Perspective on The Use of Sevima Edlink as an English Learning Medium - Laili, Roudlotun Nurul; Nashir, Muhammad; Kifi, Achmad (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
In this modern era, the use of technology in education is growing, especially after the Covid 19 pandemic, which forced the educational world to adapt to technology so that learning can continue even though it is limited by space and time. So in the post-pandemic, education was used using technology, and student independence in learning has been well developed so that blended learning can be an alternative learning model in this new normal era. The Sevima Edlink application can be an alternative solution in blended learning because it is already integrated with the Siakad system on campus and can be accessed easily from a laptop and smartphone. This research aimed to describe the students’ perspective on using Sevima Edlink as an English learning medium. It was descriptive qualitative research with a total sample of 70 students who took an English subject in the odd semester of the 2022/2023 academic year at Sekolah Tinggi Ilmu Kesehatan Banyuwangi. Based on the questionnaire results, student perceptions of using Sevima Edlink were generally positive. Interview results showed that the Sevima Edlink made the students easier to download learning materials, collect assignments more disciplined, and save data storage. Even though there were obstacles, including internet connection and weak signal, lack of information on using Sevima Edlink for new students, and task notifications were often late or did not appear, which caused students to be late in submitting assignments.